The Nutrilon Royal Advertisement on TV Commercial Break Discourse Analysis - Nuryanti, Dewi; Fazrin, A.T. (LingPoet: Journal of Linguistics and Literary Research, 2023)
The study is aimed to explain about the kinds of advertisement as genre function that emerges in Nutrilon Royal commercial break, to know the way Nutrilon Royal commercial break conveys the goal of advertisement, and to know the elements of advertisement that used in Nutrilon Royal commercial break. The data is Nutrilon Royal advertisement on TV commercial break that consist of picture and poetic language narration. The theories used to analyze are theories by Yule, Brown&Yule, Searle, and Cook. The result found that there is combination of pictures and sounds that related to the product, characters signify that Nutrilon Royal is one of brand of milk for children conveys TV commercial break by showing combination picture of child and nature and collecting of poetic languages, from eight elements of advertisement, only six are found: participants, function, picture, music, paralanguage, and situation. the combination of picture, poetics languages as narration and back sound convey important purpose of TV commercial break.